Kepimpinan daripada pelbagai perspektif dalam konteks Malaysia - Malike Ibrahim; Marwan Ismail; Musliza Mohamad (Penerbit Universiti Malaysia Kelantan, 2017)
This book seeks to collect various issues in leadership in Malaysia that can be evaluated from various perspectives such as politics, administration, organizations, youth, financial and banking institutions.